Transformation of tall-tussock grasslands and soil water dynamics in the Flooding Pampa - Sirimarco, Marina Ximena (2023)
Cow-calf production is the main practice within marginal agricultural lands of the world, like the Flooding Pampa of Argentina, where it promotes the transformation of native tall-tussock grasslands Paspalum quadrifarium into native short-grass grasslands or sown pastures. The effect of these land use changes on water dynamics are not well understood, especially in regions subjected to marked interannual drought and flooding cycles. Here we measured soil properties (infiltration rate, bulk density and soil organic matter), rainfall interception by the canopy, and soil moisture during two years with different annual rainfall. Then, we parameterized a hydrological model (HYDRUS) for inferring consequences of soil water fluxes on water regulation. Infiltration rate was significantly higher in native tall-tussock grasslands than native short-grass grasslands and sown pastures, bulk density was significantly lower in native tall-tussock grasslands than native short-grass grasslands and sown pastures, and soil organic matter was significantly higher in native tall-tussock grasslands than sown pastures. Simulated water dynamics during years of low annual precipitation (summer rainfall deficit), show that transpiration and evaporation from native short-grass grasslands represented 59 % and 23 % of total water balance, whereas transpiration and evaporation from native tall-tussock grasslands represented 70 % and 12 %, respectively. This result reflects the high productive capacity of native tall-tussock grasslands under dry conditions. In contrast, under high annual precipitation (excess during fall and winter), transpiration and evaporation from native short-grass grasslands represented 48 % and 26 % of total water balance, whereas in native tall-tussock grasslands represented 35 % and 9 %, respectively. These results suggest a low capacity of native tall-tussock grasslands to evacuate water excess, especially during fall and winter. The observed differences in water fluxes between native tall-tussock grasslands and native short-grass grasslands are important to understand water dynamics under different climatic conditions and could be useful for adaptation to climate change through ecosystem-based management.